E-167 Imaging optimization for flow diversion in c-arm cone beam computed tomography. (4th August 2020) - Dornbos, D; DiNitto, J; Elijovich, L; Hoit, D; Inoa-Acosta, V; Nickele, C; Duckworth, E; Arthur, A
Abstract : Introduction: Contrast usage for Cone Beam Angiographic Computed Tomography (CBCTA) performance has limited efficacy for simultaneous visualization of vasculature, implanted devices, and surrounding tissue. Optimal windowing of CBCTA images in order to simultaneously visualize both low attenuating brain parenchyma and high attenuating flow diverters remains a significant challenge. Appropriate dilution of contrast has the potential to reduce the gray scale value on the vasculature and allow enhanced simultaneous visibility of tissue and parent artery. Currently, there has been limited work donepertaining to optimal contrast dilution in CBCTA. 1 2 We present an in vivo study aimed to identify optimal contrast dilution to improve image quality in the setting of flow diverting stents. Methods: Cone beam CT-based computed angiographic imaging (20 s DR, Syngo DynaCT, Siemens Healthineers, Forchheim, Germany) was performed on 10 patients following placement of a Pipeline (Medtronic USA) flow diverting stent. Cone beam CT imaging was acquired with selective internal carotid artery catheterization utilizing 5 different contrast percentages (5, 10, 15, 20, and 25%) with a constant flow rate of 3 mL/sec and 80 cc of contrast. Gray scale values were averaged for pertinent structures (parent artery, Pipeline device, bone, and background) using region of interest (ROI) analysis of respective Hounsfield units. Contrast to noise ratio (CNR) was used for measurement. Contrast dilution that allows matched CNR in both bone and the parent artery provides ideal visualization. Results: In the 10 patients evaluated in this study, evaluation of bone and parent vessel CNR identified 15% contrast as optimal for visualization of the Pipeline embolization device within the parent artery (figure 1A ). Other contrast concentrations had greater observed differences between bone and parent vessel CNR (figure 1B ) and decreased visualization of the flow-diverting device. Conclusion: The concentration of contrast administered during Cone Beam Angiographic Computed Tomography has a substantial impact on the attenuation of surrounding structures (bone, parenchyma), which can impair simultaneous visualization of the parent vessel and implanted device. Based on this analysis, 15% contrast dilution optimizes visualization of the Pipeline embolization device and its position within the parent artery. References: Duckworth, et al., Optimizing contrast-enhanced cone-beam CT protocol to facilitate simultaneous visualization of neurovascular pathologies and surrounding structures of interest. Interventional Neuroradiology 2019;7(1):102–110. DiNitto, et al., Optimization of device visualization for C-arm conebeam computed tomography in the angiography suite. Journal of Neurointerventional Surgery 2018;10:A80. Disclosures: D. Dornbos: None. J. DiNitto: 5; C; Siemens Medical Solutions. L. Elijovich: 1; C; Siemens Medical Solutions. D. Hoit: 1; C; Siemens Medical Solutions. V. Inoa-Acosta: 1; C; Siemens Medical Solutions. C. Nickele: 1; C; Siemens Medical Solutions. E. Duckworth: None. A. Arthur: 1; C; Siemens Medical Solutions.